Mythology and Nation Building N.F.S. Grundtvig and His European Contemporaries - Stahl, Pierre-Brice; Kolle Martinsen, Lone; Bonding, Sophie (Book collections on Project MUSE., 2021)
This interdisciplinary anthology offers new perspectives on the role of pre-Christian mythologies in the formation of national communities in 19th Century Europe. Through a combination of theoretical articles and case studies, it provides new understandings of how intellectual and cultural thinkers across Europe used pre-Christian mythologies as a resource for forging their respective national communities.